Models and algorithms for the refinement of therapeutic approaches for retinal diseases - Friedmann, Elfriede; Dörsam, Simon; Auffarth, Gerd U. (Diagnostics, 2023)
We are developing a Virtual Eye for in silico therapies to accelerate research and drug development. In this paper, we present a model for drug distribution in the vitreous body that enables personalized therapy in ophthalmology. ...
Gesehen am 07.12.2023